2017
DOI: 10.1016/j.jcrc.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory pathogen colonization of dental plaque, the lower airways, and endotracheal tube biofilms during mechanical ventilation

Abstract: To the best of our knowledge, this is the largest study to date exploring oral microbial changes during both mechanical ventilation and after recovery from critical illness. Based on these findings, it was apparent that during mechanical ventilation, dental plaque represents a source of potential VAP pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 61 publications
2
63
0
8
Order By: Relevance
“…Oral bacteria may be transferred to the lower airways in patients fitted with orotracheal tubes and cause pneumonia associated with MV. This finding was reported in a study that identified the presence of S. aureus and P. aeruginosa, which are potential respiratory pathogens, in oral biofilm 25 .…”
supporting
confidence: 72%
“…Oral bacteria may be transferred to the lower airways in patients fitted with orotracheal tubes and cause pneumonia associated with MV. This finding was reported in a study that identified the presence of S. aureus and P. aeruginosa, which are potential respiratory pathogens, in oral biofilm 25 .…”
supporting
confidence: 72%
“…18 In this study, respiratory pathogens, such as Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa, Table 2. Distribution of pathogens identified in the first (at admission) oral collection of patients on mechanical ventilation in the adult intensive care unit according to the pulmonology evolution of the patient.…”
Section: Discussionmentioning
confidence: 97%
“…Commensal oral bacteria like S. aureus colonise the tracheostomy tube lumen and may lead to Ventilator associated pneumonia (VAP). (14) In the current ongoing study, a comparison has been done between antibiotic sensitivity of biofilm producing and nonbiofilm producing microorganisms. In biofilm producing K. pneumoniae, cephalosporins, aminoglycosides, few of the carbapenems and fluoroquinolones were resistant and the most effective drug came out to be Tigecycline and Colistin ( Figure: 1).…”
Section: Discussionmentioning
confidence: 99%